urbanization trends - Grigoryeva, Elena; Lidin, Konstantin (project baikal, 2021)
Sometimes, people dream ofBlue cities,Which have no name.Song from the film “Two Sundays”, 1963What does the future hold for us? This question has always attracted attention and always eluded answering. Which of today’s trends will shape the appearance of tomorrow's cities? Irkutsk architects, continuing the theme of the Winter City, reflect on the development of underground urbanism. Novosibirsk citizens study the creative capital as the main resource for the growth of Siberian cities. The environmental approach to urban development and the ratio of the notion of environment with the borderline concepts of style, meaning and essence are studied by theorists of architecture. The issues of the theory are directly related to everyday practice of the post-covid world. Isolation of people from each other and fusion of residential spaces with the office ones, new functions and the role of public spaces need reflection right now. The triptych of philosophers from Voronezh, Latvia and Vologda is about it.
Keywords: trends; underground urbanism; environmental approach